Drawing the unfixed - Twose, Simon; Moloney, Jules; Globa, Anastasia; Harvey , Lawrence (Interstices: Journal of Architecture and Related Arts, 2022)
This article reflects on creative practice employing multi-modal architectural drawing to sketch natural phenomena: expanded drawing. The work explores unfixed, intangible conditions within phenomena, conditions at the cusp of awareness, spatially felt as much as known by other means. Through multi-sensory drawing installations, phenomena such as oceanic immensity, seismic latency, and shapeshifting bushfires are sketched. The installations immerse participants within virtual, sculptural, and sonic sketches, intensifying phenomena’s abstract presence in a sympoiēsis of human and more-than-human dynamics. Three projects in the series are reflected upon as to their strategies for capturing unfixed conditions in expanded, hybrid sketches. Architectural drawing’s traditional openness, material dynamics, and capacity for imaginative projection, are shown to be intensified, through physical and digital sketch media, crossing unfixed drawing with unfixed phenomena.